A discretized linear elastic model for cloth buckling and drape - Dias, J.; Gamito, M. N.; Rebordão, J. M. (Textile Research Journal, 2000)
We present a computational model for plain woven fabrics. The model is able to represent known elastic behavior in deformation such as planar extension, shearing and out-of-plane bending, drape, and buckling. Buckling behavior is present both in shear and compression. The cloth is assumed to be an orthotropic linear elastic continuum, discretized by a mesh of triangles. Each triangle links three particles and is able to measure the stress and strain of the underlying medium. For the planar deformation, we assume the hypothesis of the plate under plane stress from the classical theory of elasticity. For the out-of-plane deformation, we allow linear elasticity and nonlinear displacement in bending, by modeling curvature interactions along the edges of neighboring triangles. To formulate the dynamic equilibrium of the mechanical system, we use Newton's second law. Nonlinear elastic material behavior is made possible by piecewise linear approximation of measured data. Visual results of cloth under various deformation conditions are presented—in tensile, draping, and buckling situations.